Civil society through the lifecourse - Power, Sally, (Civil society and social change, 2020)
Are young people blindly self-interested? How does university shape students' political participation? Can busy parents and grandparents find time to volunteer? Challenging conventional thinking, leading academics explore how individuals' relationships with civil society change over time as different lifecourse events and stages trigger and hinder civic engagement. Drawing on personal narratives, longitudinal cohort studies and national surveys, this unprecedented study considers rarely examined aspects of civic engagement including school students' sense of social responsibility and the charitable legacy bequests of elderly people and highlights significant implications for those promoting greater civic and political participation.